Legalitas Kedudukan Kontrak Sewa Kandungan Dalam Perspektif Hukum Perdata di Indonesia - Rizky Ariesandhy Kurnia Prastiono; Widhi Handoko (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractThe phenomenon of the presence of a surrogate mother in the midst of a husband and wife who longs for a descendant has become widespread in Indonesia. Many married pasangans who are biologically unable to produce children are willing to take this step. This study aims to examine the legality aspect of the Substitute Mother phenomenon from the perspective of civil law. This research was conducted with a normative juridical method. In relation to the surrogate mother, this creates a problem because Indonesia does not yet have a valid fundamental law on how to do it, and it is permissible or not. However, even though there are no rules regarding the establishment of surrogate mothers in the Indonesian law, there are several positive laws that may touch on the surrogate mother contract, namely the Civil Code, Law No. 36 of 2009 on health, and regulations. in Islamic Law. However, on the other hand, the legality of the procedure is still questionable because it involves the rights of the children born in the agreement. The indications of thought in children's rights have become one of the debates in the community. Indonesia does not have a specific regulation regarding surrogacy in civil law because it is related to contracts/ consensus, civil law generally regulates it, but there are several laws that can be used as role models so that this uterine rental contract does not escape legal bondage.Keywords: legality; surrogate mother; civil lawAbstrakFenomena hadirnya Ibu Pengganti di tengah-tengah sepasang suami isteri yang mendambakan seorang keturunan menjadi marak di Indonesia. Banyak pasangan suami isteri yang secara biologis tidak mampu mendapatkan keturunan, rela menempuh Langkah ini. Penelitian ini hendak meneliti tentang aspek legalitas dari fenomena Ibu Pengganti ini dari persepektik hukum perdata. Penelitian ini dilakukan dengan metode yuridis normative. Dalam kaitannya dengan Ibu Pengganti ini menimbulkan masalah yang disebabkan karena di Indonesia belum memiliki hukum fundamental yang sah tentang cara melakukannya, dan boleh atau tidak. Namun meski demikian, meski tidak ada aturan tentang pendirian ibu pengganti dalam Undang-Undang Indonesia, ada beberapa hukum positif yang mungkin menyinggung perihal kontrak ibu pengganti yaitu Kitab Undang-Undang Hukum Perdata, Undang-Undang No 36 Tahun 2009 tentang kesehatan, dan dan Regulasi dalam Hukum Islam. Namun di sisi lain, prosedur tersebut masih dipermasalahkan kehalalannya karena menyangkut hak buah hati yang dilahirkan dalam pemufakatan tersebut.Indikasi pengikiran dalam hak buah hati menjadi salah satu perdebatan dalam kalangan masyarakat.Indonesia tiada ada mengatur secara spesifik mengenai surogasi dalam hukum perdata karena terkait kontrak/pemufakatan,hukum perdatalah yang secara umum mengaturnya,namun ada beberapa undang-undang yang bisa dijadikan panutan agar kontrak sewa rahim ini tidaklah lolos dari jeratan hukum.Kata kunci: legalitas; kontrak sewa kandungan; hukum perdata